2021
DOI: 10.3389/fpls.2021.671026
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Physiological Responses and Secondary Metabolites Modulation by Preharvest Factors of Three Hydroponically Grown Genovese Basil Cultivars

Abstract: Sweet basil (Ocimum basilicum L.) is an economically important leafy vegetable especially in Mediterranean countries. In Italian gastronomy, the large elliptical leaves of the Genovese type are mostly used for the well-known pesto sauce, and almost all (>90%) professional production is for the food industry. The growing demand for fresh leaves with standardized technological and sensory characteristics has prompted basil producers to adopt advanced cultivation methods such as the floating raft system (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 67 publications
4
23
0
Order By: Relevance
“…In our work, high salinity levels (High Mix and High NaCl) reduced β-linalool, probably due to the depression of carbon assimilation required to produce VOCs, as inferred from the reduced DW ( Table 2 ). As is known in the literature, mutable conditions after the cut had a greater influence on the quality of the aroma profile ( Table 6 ; Zheljazkov et al, 2008 ; Corrado et al, 2020a ; Ciriello et al, 2021a , b ). Specifically, the two basil cultivars responded differentially to the successive cuts, with an increase in β-myrcene and β-ocimene and a reduction in eucalyptol observed in Green, while an increase in β-linalool was observed in Red.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In our work, high salinity levels (High Mix and High NaCl) reduced β-linalool, probably due to the depression of carbon assimilation required to produce VOCs, as inferred from the reduced DW ( Table 2 ). As is known in the literature, mutable conditions after the cut had a greater influence on the quality of the aroma profile ( Table 6 ; Zheljazkov et al, 2008 ; Corrado et al, 2020a ; Ciriello et al, 2021a , b ). Specifically, the two basil cultivars responded differentially to the successive cuts, with an increase in β-myrcene and β-ocimene and a reduction in eucalyptol observed in Green, while an increase in β-linalool was observed in Red.…”
Section: Discussionmentioning
confidence: 52%
“…The gas chromatography/mass spectrometry (GC/MS) analysis showed that the aroma profile of Red and Green basil was predominantly characterized by eucalyptol ( Table 6 ), in contrast to several studies in which β-linalool was the most abundant compound ( Marotti et al, 1996 ; Ciriello et al, 2021a , b ). This variation in the volatile composition may derive from the interaction of pre-harvest factors such as cultivar, environmental conditions, and cultural practices ( Farsaraei et al, 2020 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Among the different hydroponic techniques, the floating raft system (FRS) has become the most successful for producing leafy vegetables such as lettuce, basil, rocket, and radish [13,14]. Compared to conventional soil-based cultivation, FRS guarantees the (i) de-seasonalization of production, (ii) speeding up the growth cycle, (iii) increment of water use efficiency, (iv) reduction of labor costs, (v) increment of unit production through higher planting density, (vi) achievement of more stable and repeatable growth conditions, (vii) reduction of the incidence of telluric pathogens, and (viii) overcoming of the limiting conditions such as high salinity, heavy metal contamination, and suboptimal soil reactions (alkalinity and acidity) [5,8,[13][14][15]. FRS bestows a benefit for both consumers and fresh-cut vegetable growers who can produce residue-free soil products, which results in fewer washing procedures with less water waste [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Minor plant species, such as herbs, due to a heterogeneous and not fully explored reservoir of secondary metabolites, have rekindled the interest of both consumers and academics ( Kwon et al, 2020 ; Alexopoulos et al, 2021 ). Basil ( Ocimum basilicum L., Lamiaceae ) is an irreplaceable ingredient for traditional Italian dishes (“pesto” and pizza “Margherita”) and the pharma-cosmetic sector ( Barátová et al, 2015 ; Ciriello et al, 2021a , b ) due to the biosynthesis of low molecular weight organic compounds (i.e., monoterpenes and phenylpropanoids), responsible for its distinctive aroma ( Dias et al, 2016 ). On the other hand, the outstanding nutraceutical value of basil is mainly attributable to a heterogeneous phenolic profile (rosmarinic acid, chicoric acid, caffeic acid, and p-coumaric acid) that, like aroma, is strongly affected by the interaction between genotype and environment ( Jakovljević et al, 2019 ; Ciriello et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%